2020
DOI: 10.1177/0886260520957978
|View full text |Cite
|
Sign up to set email alerts
|

“When Her Visa Expired, the Family Refused to Renew It,” Intersections of Human Trafficking and Domestic Violence: Qualitative Document Analysis of Case Examples from a Major Midwest City

Abstract: This study aimed to further understand typologies of trafficking that occur in the home, by an individual’s intimate partner (IP) or family members and this overlap with extant knowledge on perpetrator manipulation via the Power and Control Wheel. Inductive and deductive techniques were used to analyze secondary data from a federally funded anti-trafficking program in a Midwest metropolitan area recorded between 2008 and 2017. Cases were included if there was indication of sex or labor exploitation initiated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
1
5
0
1
Order By: Relevance
“…This is the first study of which we are aware that links experiences of DMST to nonsexual interpersonal violence victimizations in adolescence using a large, population-based survey. These findings are consistent with other studies that have shown a connection between trafficking and other forms of violence, such as partner or domestic violence, and they reinforce the notion that DMST is not an isolated form of violence in the lives of minors (Koegler et al, 2020;Ortega-Senet & Tierney, 2020). This work also builds on prior Add Health analyses which found that DMST experiences were significantly linked to forced sex in adolescence, though it is unclear in these previous analyses whether respondents were considering their DMST experiences as forced sex or if the reported forced sex reflected one or more separate experiences from DMST (Edwards et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study of which we are aware that links experiences of DMST to nonsexual interpersonal violence victimizations in adolescence using a large, population-based survey. These findings are consistent with other studies that have shown a connection between trafficking and other forms of violence, such as partner or domestic violence, and they reinforce the notion that DMST is not an isolated form of violence in the lives of minors (Koegler et al, 2020;Ortega-Senet & Tierney, 2020). This work also builds on prior Add Health analyses which found that DMST experiences were significantly linked to forced sex in adolescence, though it is unclear in these previous analyses whether respondents were considering their DMST experiences as forced sex or if the reported forced sex reflected one or more separate experiences from DMST (Edwards et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Traffickers may exert control through blackmail, fraud or deception, and/or violence. 42,45,92,95 By alternating acts of violence and cruelty with acts of kindness and "love," a trafficker may build strong bonds with children and adolescents, making it very difficult for youth to leave the situation. 22 Individuals experiencing labor or sex T/E may not recognize their situation as exploitative, instead feeling that they "owe" their traffickers obedience because of previous kind behaviors or because of an exorbitant debt.…”
Section: Risk Factors For Labor and Sex Trafficking And Exploitationmentioning
confidence: 99%
“…In this vein, researchers have suggested the need to assess risk factors beyond individual and familial levels among runaway youth victims of commercial sexual exploitation, since older dating partners are uniquely associated with this victimisation (Fedina et al, 2019b). Other studies have identified intimate partners such as boyfriends, fiancés, husbands, or fathers of women's children as abusers and exploiters of sex trafficking victims through force or coercion, including isolation, physical abuse and sexual abuse (Koegler et al, 2020).…”
Section: Influence Of Intimate Relationshipsmentioning
confidence: 99%
“…In addition, there may be similarities between the coercive and manipulative mechanisms exerted by traffickers towards victims recruited through intimate relationships and domestic violence dynamics (Raymond and Hughes, 2001). In these cases, sexual exploitation, IPV and domestic violence may overlap (Koegler et al, 2020).…”
Section: Influence Of Intimate Relationshipsmentioning
confidence: 99%